Creation of the Poster “Masterpiece of West Java Culture” as a Representation of Sundanese Cultural Identity - Bermana, Ary Leo; Victory, Well (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2025)
The creation of the poster “Masterpiece of West Java Culture” stems from the richness of Sundanese tradition, particularly “wayang golek”, which combines visual performance with oral heritage. The primary aim of this creation is to present a poster as a representation of Sundanese cultural identity through a reinterpretation of the oral essence and symbolic philosophy of “wayang golek” into a contemporary visual language. The creative process was carried out using a practice-based method that included exploration, experimentation, and visual recontextualization. The traditional forms and narratives of “wayang golek” were studied and transformed into modern graphic expression without eliminating their cultural depth. One significant visual decision was the use of eye colors—blue and red—symbolizing tranquility and wisdom on one hand, and vitality and passionate energy on the other. This duality reflects the philosophical values of balance and harmony deeply rooted in Nusantara culture. The resulting creation produced the poster ‘Masterpiece of West Java Culture”, which functions not only as a visual artifact but also as a cultural statement. This work bridges oral tradition with contemporary design, offering a new perspective for international audiences to appreciate Sundanese cultural identity in the modern era.